2013
DOI: 10.1182/blood-2013-04-495598
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitor usage, treatment outcome, and prognostic scores in CML: report from the population-based Swedish CML registry

Abstract: Key Points• Patients up to age 70 years with CML treated within a decentralized health care setting had a relative survival close to 1.0. • Sokal, but not EUTOS, score at diagnosis predicted overall and relative survival in a population-based cohort of patients with CML.Clinical management guidelines on malignant disorders are generally based on data from clinical trials with selected patient cohorts. In Sweden, more than 95% of all patients diagnosed with chronic myeloid leukemia (CML) are reported to the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
121
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 29 publications
13
121
4
2
Order By: Relevance
“…There is clear evidence that survival (Hoglund et al 2013) of CML patients is close to the age-matched general population and also quality of life in the aged-matched general population is similar for most CML patient groups (Efficace et al 2011) when CML is treated effectively in chronic phase with current therapies. However, every fifth patient is classified as having "low adherence" according to the MMAS.…”
Section: Discussionmentioning
confidence: 99%
“…There is clear evidence that survival (Hoglund et al 2013) of CML patients is close to the age-matched general population and also quality of life in the aged-matched general population is similar for most CML patient groups (Efficace et al 2011) when CML is treated effectively in chronic phase with current therapies. However, every fifth patient is classified as having "low adherence" according to the MMAS.…”
Section: Discussionmentioning
confidence: 99%
“…This translocation, leading to a new, hybrid, leukemia-specific gene (BCR-ABL1) encoding for a deregulated tyrosine-kinase protein (p210), drives the leukemic transformation of hematopoietic stem cells [1][2][3][4][5][6] and induces the progression of the disease from the early chronic phase (CP) to the late blastic phase BP) which close the natural history of the disease.…”
Section: Short Communicationmentioning
confidence: 99%
“…There are several studies that provide estimates of the underlying distribution of disease progression risk scores in newly diagnosed CML patients. Clinical trials and real-world registry data have consistently shown that approximately two-thirds of patients are at intermediate or high risk of disease progression at diagnosis (Figure 1) [14][15][16]. Implementing generic imatinib step edits irrespective of disease progression risk level is inconsistent with the NCCN guidelines and has the potential to compromise clinical outcomes of a large proportion of CML patients.…”
Section: Generic Imatinib Step Editmentioning
confidence: 99%